Dermoscopic Examination in Malassezia folliculitis - ahmad, zahruddin; Ervianti, Evy (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Malassezia folliculitis (MF) is the most common fungal folliculitis, and it is caused by yeast of the genus Malassezia. MF may be difficult to be distinguished clinically from acne and other types of folliculitis, causing misdiagnosis and improper treatment. Dermoscopy has been very useful to support the diagnosis of several types of folliculitis, including MF. Purpose: To know the role of dermoscopic examination in MF. Review: The diagnosis of MF can be identified by usual clinical presentation with direct microscopy and culture of the specimen, Wood's light examination, histopathological examination, and rapid efficacy of oral antifungal treatments. Several studies reported that dermoscopy provides a deeper level of the image that links the clinical morphology and the underlying histopathology. Some dermoscopic patterns are observed consistently with certain diseases, including MF, so these could be used for establishing their diagnosis. The dermoscopic features of MF seem to correlate with the current understanding of its etiopathogenesis. Conclusion: Dermoscopic examination in MF will reveal dermoscopic patterns including folliculocentric papule and pustules with surrounding erythema, dirty white perilesional scales, coiled/looped hairs with perifollicular erythema and scaling, hypopigmentation of involved hair follicles, and dotted vessels.